Evaluating wheat for genetic variation in radiation use efficiency: scaling traits from leaves to canopies - Robles-Zazueta, Carlos Alfredo (2022)
Wheat yields are stagnating or declining in many regions of the planet, requiring efforts to improve the light conversion efficiency, i.e., radiation use efficiency (RUE). RUE is a key trait in plant physiology because it links light capture and primary metabolism with biomass accumulation and yield. High-throughput phenotyping (HTP) was used among a population of field grown wheat with variation in RUE and photosynthetic traits to build predictive models of RUE, biomass and intercepted photosynthetically active radiation (IPAR). The use of remote sensing models predicted RUE with up to 70% accuracy compared to ground truth data. Wheat yield can be defined as the product of solar radiation intercepted throughout the crop cycle, radiation use efficiency and harvest index. Photosynthesis is a central component of RUE but normally measured in the upper layers of the canopy where light conditions are saturating. Significant relationships were found between light saturated photosynthetic rates measured at initiation of booting in the top, middle and bottom layers of the canopy and yield. These findings indicate that there is an opportunity for yield improvement if we consider the requirements of photosynthesis in the middle and bottom layers of wheat canopies where conditions are not light saturating. The study of photosynthesis in the field is constrained by low throughput and lack of integrative measurements at canopy level. Partial least squares regression (PLSR) modelling was used to build predictive models of photosynthetic, biophysical and biochemical traits at the top, middle and bottom layers of wheat canopies. The combined layer model predictions performed better than individual layer predictions. Using HTP allowed us to increase phenotyping capacity 30-fold compared to conventional phenotyping methods and our models can be used to screen varieties for high and low RUE. There is clear consensus in the physiological and breeding communities that improving RUE will be key to boost wheat yield. In the previous years of RUE research little has been explored on the role of root biomass accumulation and its interaction with aboveground biomass accumulation, RUE and yield. Strong positive associations were found between above and belowground biomass accumulation with RUE and root biomass during the vegetative period, and negative associations between yield components and root biomass accumulation, suggesting there is a coordination between roots and shoot in the vegetative period to maximize growth. However, if too much energy is invested in root biomass this will have an effect in decreasing aboveground biomass during grain filling. More research will be needed to explore new hypothesis in the field that accounts the effect of root biomass in canopy RUE and yield.